Utilization of the Arabic-Language Library Collection by Students in the Arabic Language Education Department at UIN Raden Intan Lampung - Umi Nur Azizah, Umi Nur Azizah; Nadirsah Hawari; Rahmat Iqbal (Jurnal El-Pustaka, 2026)
The UIN Raden Intan Lampung Library has a collection of 1,574 Arabic-language items, consisting of textbooks, dictionaries, classical texts, scholarly journals, and other Islamic reference materials to support the needs of students in the Arabic Language Education Department. This study aims to determine the utilization of the library’s Arabic-language collection and the factors that influence it. This study employed a field research method with a descriptive approach. Data were collected through observation and interviews with 15 students in the Arabic Language Education Department for the 2024 academic year, selected using purposive sampling based on the following criteria: active students as evidenced by possession of a Student ID Card (KTM), having visited the library at least 10 times in a month, and a history of borrowing books from the library at least 10 times, as evidenced by borrowing records and documentation. Data analysis techniques used include: data reduction, data presentation, and conclusions or verification. Based on the series of research findings and discussions outlined above, conclusions can be drawn. Overall, the results of the interviews and observations indicate that the factors influencing the utilization of the Arabic-language library collection at UIN Raden Intan Lampung stem not only from library facilities but are also influenced by students’ learning habits, Arabic language proficiency, digital literacy levels, and participation in information literacy activities. These factors are interrelated and influence the level of library collection utilization by students in the Arabic Language Education Department. Therefore, efforts are needed to enhance literacy culture, provide training in the use of digital resources, and strengthen Arabic language proficiency so that the utilization of the library collection can be optimized.